B09 Caspase-6 does not contribute to the proteolysis of mutant huntingtin in the HDHQ150 knock-in mouse model of Huntington's disease. (29th August 2012) - Landles, C; Smith, D; Weiss, A; Franklin, S; Howland, D; Bates, G
Abstract : Huntington's disease (HD) is a late-onset progressive neurodegenerative disorder characterised by irrepressible motor dysfunction, cognitive decline and psychiatric disturbances for which there is no effective disease-modifying treatment. The proteolytic cleavage of huntingtin (HTT) to generate N-terminal fragments has been proposed to be a key aspect of HD pathogenesis. In particular, it has been shown that HTT can be cleaved at amino acid 586 by caspase-6 (CASP6) and that prevention of cleavage at this site is neuroprotective and can rescue HD-related phenotypes in YAC transgenic HD mouse models. To further explore the role that CASP6 plays in HTT proteolysis, we have evaluated the effects of the genetic ablation of CASP6 in the HdhQ150 knock-in mouse model of HD. Here we show that the loss of CASP6 has no effect on the proteolysis of HTT, and does not modify the pattern of N-terminal HTT fragments that are present in the brains of these animals. Furthermore, we show that CASP6 ablation does not influence the steady-state levels of soluble wild type or mutant HTT in the brains of presymptomatic mice. Therefore, we conclude that CASP6 inhibition does not modify HTT proteolysis in the HdhQ150 mouse model of HD, and that targeting CASP6 as a therapeutic strategy should be approached with caution in the context of this complex disease.